Stability of physicochemical and microbiological properties of Geniotrigona thoracica honey after moisture reduction and long-term storage in different containers - Mohamad Ghazali, Nashratul Shera; Chin, Nyuk Ling; Othman, Siti Hajar; Chang, Lee Sin; Mohd Baroyi, Syahrul Anis Hazwani; Yusof, Yus Aniza (Academic Press, 2024)
Stingless bee honey is nutritious but prone to fermentation due to high moisture content and improper storage, leading to quality deterioration. This study investigates the impact of container types and storage time on the properties of minimally treated Geniotrigona thoracica honey using clay pots. The moisture content of the raw honey was reduced from 28.2 g/100 g to 19.5 g/100 g after clay pot storage. The treated honey was then divided into four different containers: glass jars (clear and amber) and polyethylene terephthalate jars (clear and amber), and stored at 27 ± 2 °C for 365 days. After 365 days, moisture content slightly decreased in all containers, with honey in amber glass jar showing the lowest at 16.8 g/100 g. As moisture decreased, TSS increased, indicating sugar concentration. Ash content, viscosity, and free acidity increased over time, while pH values slightly decreased but stayed within acceptable limits. Honey colour increased with honey in amber glass jar showed the darkest honey (286 ± 2 mm Pfund) after 365 days. For all samples, the total phenolic content increased indicating enhanced antioxidant properties. While the hydroxymethylfurfural level increased but remained within standards with honey stored in amber PET jar had the lowest level (10.8 ± 0.2 mg/kg). Overall, moisture reduction with clay pots and proper storage containers can maintain and enhance honey quality during extended storage, with all samples meeting quality standards throughout.